KDM2A Targets PFKFB3 for Ubiquitylation to Inhibit the Proliferation and Angiogenesis of Multiple Myeloma Cells - Liu, Xinling; Li, Jiaqiu; Wang, Zhanju; Meng, Jie; Wang, Aihong; Zhao, Xiaofei; Xu, Qilu; Cai, Zhen; Hu, Zhenbo (Frontiers in Oncology, 2021)
The lysine demethylase KDM2A ( also known as JHDM1A or FBXL11) demethylates histone H3 at lysine K36 which lead to epigenetic regulation of cell proliferation and tumorigenesis. However, many biological processes are mediated by KDM2A independently by its histone demethylation activity. In the present study, we aimed to characterize the functional significance of KDM2A in multiple myeloma (MM) disease progression. Specifically, we defined that one of the key enzymes of glycolysis PFKFB3 (6-phosphofructo-2-kinase) is ubiquitylated by KDM2A which suppresses MM cell proliferation. Previous study showed that KDM2A and PFKFB3 promoted angiogenesis in various tumor cells. We further reveal that KDM2A targets PFKFB3 for ubiquitination and degradation to inhibit angiogenesis. Several angiogenic cytokines are also downregulated in MM. Clinically, MM patients with low KDM2A and high PFKFB3 levels have shown worse prognosis. These results reveal a novel function of KDM2A through ubiquitin ligase activity by targeting PFKFB3 to induce proliferation, glycolysis and angiogenesis in MM cells. The data provides a new potential mechanism and strategy for MM treatment.